Rehabitar nuestra casa: Un reto Eco-Ético ante la emergencia ambiental planetaria (2011)
This article is about an existing need nowadays to make education support the human being’s integral formation who can  understand and be aware of the full relationship between the man and those cosmic avatars and the endless micro-organisms that regulate the acting and the evolutionary process of these macrocosms; to lead this process, it is proposed that education restores a perspective of human values which lets the man recover his own dignity as well as his intimate relationship with nature, and in this sense, his anthropology priority can go from the brushstrokes of a harmonic relationship to the ecological perspective of the polyphonies which have understood that the object, opposite to the pressing environmental reality, is to establish an ethical way to reinhabit our Earth.